(untitled) (UUM Journal of Legal Studies, 2016)
Domestic violence is a social epidemic in Malaysia. To combat this, the Domestic Violence Act 1994 and the Domestic Violence (Amendment) Act 2012 has set up a mechanism via the Malaysian criminal justice system to investigate reports, prosecute the perpetrators and protect the victims of domestic violence. Unfortunately, the mechanism has been viewed with disfavor by many. This paper attempts to critically appraise the effectiveness of the mechanism and subsequently propose an alternative method to better deal with domestic violence cases. Applying a descriptive and analytical approach in data analysis, the paper concluded that the mechanism currently being implemented in dealing with domestic violence cases is ineffective and ineffectual. Therefore a specialized court (instead of the current criminal court) which deals specifically with domestic violence is suggested. Keywords: Domestic violence; women; domestic violence court